Social and Cognitive Interactions Through an Interactive School Service for RTT Patients at the COVID-19 Time - Dovigo, Lucia; Caprì, Tindara; Iannizzotto, Giancarlo; Nucita, Andrea; Semino, Martina; Giannatiempo, Samantha; Zocca, Lia; Fabio, Rosa Angela (Frontiers in Psychology, 2021)
Background: The closure of all educational institutions and most rehabilitation centres represents a precautionary measure to face the COVID-19 pandemic, but the isolation and social distancing may be particularly challenging for children with special needs and disabilities (SEND), such as Rett Syndrome (RTT). The main aim of this study was to promote cognitive and social interactions among children with RTT through an interactive school program. Methods: The Interactive School palimpsest was composed of moments in which a teacher spoke directly to children with RTT and expected a response through eye gaze, and moments in which stories-cartoon were presented while tracking the eye gaze of children. We investigated behavioural, social and cognitive parameters. Results: Children participated in both social and cognitive tasks with the spontaneous reduction of stereotypies and with increase in attention. They recalled more significant indexes when music or a song was presented together with a cartoon or a cognitive task. Conclusions: This study provides initial insights in promoting cognitive and social interactions and in the support needs of families with a child with RTT during the COVID-19 pandemic.